PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS QUIZIZZ DAN GOOGLE SLIDES - Afdi Fauzul Bahar; Bella Tasya Kumala Dewi; Ejah Said Mansur; Maria Ulfah Siregar (Aplikasia)
The COVID-19 pandemic has revolutionized the learning process, including online learning which requires educators to be more adaptive and innovative in teaching. Educators, especially teachers, must master the latest technology and learning methods, especially with the challenges in the post-pandemic era, where students tend to prefer the Learning by Doing approach. This community service activity is a Quizizz and Google Slides training for Teachers at SMA Abu Bakar IT Yogyakarta. The target of this activity is 22 educators who are community service partners. Activities are carried out offline or face-to-face consisting of presentation of materials and practices and evaluation of activities by providing training activity questionnaires. The research method used is Asset-Based Community Development (ABCD). This method can optimize organization, connect and utilize assistance from external institutions. The results of the questionnaire responses given to participants for this training activity showed positive results, this was felt because the teacher gained skills and knowledge in using the Quizizz and Google Slides platforms.